ASPEK DIDAKTIS PERAN PEREMPUAN JAWA DALAM SERAT SANDI WANITA KARYA K. G. P. A. PAKUALAM II - Shinta, Noviana Dewi; ., Darni; Ahmadi, Anas (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
The didactic aspect of women's roles is conveyed from childhood to adulthood to advance their mindset. The purpose of this research is to show and describe the didactical aspects of the role of Javanese women in Serat Sandi Wanita by K. G. P. A. Pakualam II. The method used in this research utilizes a qualitative approach, where the data used is in the form of geguritan so that the results are in the form of phrases, words, or sentences. The theory used is the theory of feminism proposed by Lori Jo Marso which states that the demands of feminism depend on the situation and conditions. The results of this study show that the socio-cultural environmental conditions taught in SSW rely on the teachings of the kraton that a woman wants to do, where a woman plays a role as a child, wife, and mother. As a child obeying parents, behaving well, making parents happy and not favoring himself. As a wife, she respects her husband with gentle words, reminds each other, and respects her husband because he is the teacher in the household. The role of women as mothers gives advice to their children, such as having to respect their husbands when they are married, and any activity must have his permission.